Trends in Ezetimibe Prescriptions as Monotherapy or Fixed-Dose Combination in Germany 2012–2021 - Katzmann, Julius L.; Kieble, Marita; Enners, Salka; Böhm, Michael; Mahfoud, Felix; Laufs, Ulrich; Schulz, Martin (Frontiers in Cardiovascular Medicine, 2022)
Aims Addition of ezetimibe to statin therapy is recommended by current guidelines when low-density lipoprotein cholesterol (LDL-C) targets are not achieved with statin monotherapy. Fixed-dose combinations (FDC) improve medication adherence and facilitate risk factor control. We assessed prescription trends of ezetimibe as monotherapy or FDC with statins. Methods Data from the German Institute for Drug Use Evaluation (DAPI) containing dispensing data of >80% of community pharmacies were analyzed. Prescriptions over time of lipid-lowering agents at the expense of the statutory health insurance (SHI) were extrapolated to all SHI-insured persons, representing approximately 88% of the total German population. Drug utilization was expressed as defined daily doses per 1,000 SHI-insured persons per day (DID). Results Of all lipid-lowering drug prescriptions in 2021, 91.2% were statin monotherapy. Ezetimibe was prescribed as monotherapy or FDC with statin in 4.4 and 2.9%, respectively. DID steadily increased for statin (69%) and ezetimibe (424%) monotherapies between 2012 and 2021. In contrast, statin-ezetimibe FDC prescriptions exhibited only a minor increase (29%). The proportion of statin-ezetimibe FDC among all statin prescriptions was stable over time at approximately 3%. FDC prescription rates by specialists were higher compared to general practitioners and varied considerably between geographic areas. Conclusion Combination lipid-lowering therapy is prescribed to a minority of patients. Prescriptions of ezetimibe as monotherapy increased to a much greater extent than statin-ezetimibe FDC. Considering the low proportion of patients achieving their LDL-C target and improved adherence to FDC compared to separate pills, statin-ezetimibe FDC may be utilized to improve the management of dyslipidemia.